2019
DOI: 10.31296/aop.v3i7.126
|View full text |Cite
|
Sign up to set email alerts
|

Manage Stress to Tackle Mental Health Problems in the Workplace

Abstract: The number of people suffering from mental health problems in the workplace is alarming. As costs resulting from lost productivity increase, so does the need for work organizations to address mental health issues. Because stress negatively contributes to mental health, employers are encouraged to tackle mental health problems by assisting employees with stress management. In addition to creating a supportive environment, training employees on boundary and coping strategies, promoting and supporting daily recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They can include spouses, parents, colleagues, friends, superiors, and others from the workplace or family. Besides concentrating on the individual himself, past research (Kreiner et al, 2009;Mickel, 2019) has contended that other people (such as mentors) also may affect how individual negotiate the work-family boundary. Specifically, findings from this study have indicated that other people, or known as the 'border-keepers' (Clark, 2000) in informant's lives have great influence in helping and supporting informants to juggle work, family and OV work.…”
Section: Discussion On How Doctors Balance Between Their Work and Fam...mentioning
confidence: 99%
“…They can include spouses, parents, colleagues, friends, superiors, and others from the workplace or family. Besides concentrating on the individual himself, past research (Kreiner et al, 2009;Mickel, 2019) has contended that other people (such as mentors) also may affect how individual negotiate the work-family boundary. Specifically, findings from this study have indicated that other people, or known as the 'border-keepers' (Clark, 2000) in informant's lives have great influence in helping and supporting informants to juggle work, family and OV work.…”
Section: Discussion On How Doctors Balance Between Their Work and Fam...mentioning
confidence: 99%